Key components and implications of entrepreneurship: A 4-P framework - Ma, Hao; Tan, Justin (Journal of Business Venturing, 2006)
Entrepreneurship has been gaining increasing respect from the research community as a field of scholarly study as well as practical application worldwide as a means to achieve wealth creation and personal fulfillment. Yet, entrepreneurship, as a theoretical construct and practical phenomenon, remains poorly defined and its interpretation fragmented. This article attempts an eclectic account of the major ingredients of entrepreneurship and dissects the entrepreneurship process through a parsimonious 4-P framework: pioneer, perspective, practice, and performance. It is expected that this framework will help us better understand the essence of entrepreneurship: its theoretical underpinnings as well as its practical implications.